Analisis Unsur 5W+1H dan Struktur Kalimat pada Berita “Alasan 19 Mahasiswa UNIKA Diskorsing Hingga DO” - Friska Pandiangan; Dairi Sapta Rindu Simanjuntak; Elisabet Maibang; Martina Hani Simbolon; Melisa Purba; Yesa Maranata Br Bangun (PENTAS : Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study analyzes the completeness of the 5W+1H news elements and the effectiveness of sentence structure in the online news article "Reasons 19 UNIKA Santo Thomas Students Were Suspended and Expelled." The research employs a qualitative descriptive method with text analysis. Data were obtained from a news article published by Tribun Medan (December 11, 2023), which discusses disciplinary actions against 19 students due to demonstrations. Data collection techniques include reading and observing, while data analysis applies the 5W+1H framework and syntactic evaluation based on the S-P-O-K pattern. The findings reveal that the news article includes all 5W+1H elements but has some shortcomings, such as a lack of details on student violations, minimal perspectives from affected students, and potential bias favoring the university’s stance. Sentence structure analysis indicates that most sentences follow the S-P-O-K pattern, although some inefficiencies in information delivery were found. This study highlights the importance of news completeness and sentence clarity in ensuring objective information delivery. The findings are expected to serve as a reference for journalists and academics in enhancing the quality of more informative and balanced news writing.